Nanozinc Ecotoxicity in the Freshwater Invasive Bivalve Limnoperna fortunei Under a Climate Change Scenario - Ale, Analía (2025)
In a changing world where temperature is expected to increase, emerging nanopollutants could affect the biota in complex ways. With zinc oxide nanoparticles (ZnONP) being one of the most applied nanomaterials, we exposed the freshwater invasive bivalve Limnoperna fortunei to 0 (control), 25, and 250 µg/L of ZnONP at 27 or 31 °C for 96 h. In parallel, a 24 h bioassay was performed to calculate filtration rate. After 96 h, in soft tissue of the bivalves, tissue-damage-related enzyme activities (aspartate aminotransferase and alkaline phosphatase) were inhibited at both concentrations and temperatures. Oxidative stress was observed through increased superoxide dismutase activity after both ZnONP concentrations at 27 °C and decreased catalase activity after 250 µg/L at 31 °C, while glutathione-S-transferase activity showed opposing significant tendencies depending on temperature. After 6 h, the filtration rate differed significantly between control groups, as it was higher at 31 °C. However, in case of 31 °C, bivalves exposed to ZnONP drastically decreased their filtration rate compared to control. Our study highlights nanotoxicological implications of ZnONP; as even at environmentally relevant concentrations (such as the lowest applied in this study), they exert deleterious effects on freshwater organisms, which could be worsened in a climate-change scenario.